(untitled) (Vietnam Journal of Community Medicine, 2026)
Backgrounds: The Tpeak–Tend/QT (Tp–Te/QT) ratio has emerged as an electrocardiographic marker of ventricular repolarization dispersion and arrhythmic vulnerability. However, its characteristics and associated factors in hypertensive patients with heart failure remain unclear. Objectives: To describe the characteristics of the Tp–Te/QT ratio in hypertensive patients with heart failure and to identify clinical factors associated with this index. Subjects and methods: We conducted a cross-sectional study of 79 hypertensive patients with heart failure treated at the Vietnam National Heart Institute, Bach Mai Hospital, between December 2022 and October 2023. Standard 12-lead electrocardiograms were analyzed using Screen Calipers 4.0 software. Tp–Te and QT intervals were measured using the tangent method, and the Tp–Te/QT ratio was calculated across precordial leads V1–V6. Statistical analyses were performed using SPSS version 23.0. Pearson correlation was used to evaluate associations between Tp–Te/QT and clinical variables. Results: The mean age of the study population was 57 ± 12 years, and 69.6% were male. The mean Tp–Te/QT ratio across leads V1–V6 was 0.218 ± 0.023. The Tp–Te/QT ratio did not differ significantly across left ventricular ejection fraction categories or according to the presence of left ventricular hypertrophy (p > 0.05). Correlation analysis demonstrated that Tp–Te/QT was positively correlated with body weight (r = 0.28, p = 0.01), body mass index (r = 0.32, p < 0.01), and systolic blood pressure (r = 0.26, p = 0.02), and negatively correlated with serum potassium levels (r = −0.25, p = 0.02). Conclusions: In hypertensive patients with heart failure, the Tp–Te/QT ratio shows a univariate correlation with some clinical and biochemical parameters, and no significant difference is observed across the range of left ventricular ejection fraction. The Tp–Te/QT ratio may serve as a potential adjunct electrocardiographic marker in this population. Larger prospective studies are warranted to establish its clinical and prognostic value further.